PEMODELAN GEOLOGI BAWAH PERMUKAAN FASIES BATUPASIR SOKANG FORMASI ARANG, CEKUNGAN NATUNA TIMUR - , Widyo Permono, ST ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Study area is located in the southern part of the East Natuna Basin, which is one of the potentially gas-producing basins. However, exploration activity on the sandstones reservoir is not maximized. This research was conducted to determine the characteristics of sandstone facies, subsurface configuration, and subsurface geological model of Sokang Sandstone facies at the top of Arang Formation. Subsurface geological modeling of Sokang Sandstone facies is done by integrating the analysis of small-scale heterogeneity that contain information Sokang Sandstone facies model and the results of large-scale heterogeneity analysis that describes the subsurface geological conditions. Sokang Sandstone facies at the top of Arang Formation are identified as Distributary Channel facies and Distributary Mouth Bars facies. Distributary Channel facies have porosities range from 3.72 to 32.70% and a thickness of 14.87 to 48.84 feet. The Distributary Channel facies are deposited in Delta Plain sub-environment with geometric of channels trending Southwest â Northeast. Whereas, the Distributary Mouth Bars facies indicates the range of porosity from 7.14 to 36.12% with a thickness variation from 21.75 to 114.59 feet. Distributary Mouth Bars facies are deposited in Delta Front sub-environments and tends to wedge against with Distal Delta Front facies towards the basin.